Effect of Ta and W Additions on Microstructure and Mechanical Properties of Tilt-Cast Ti-45Al-5Nb-2C Alloy - Juraj Lapin; Kateryna Kamyshnykova (Metals, 2021)
The effect of Ta and W additions on microstructure and mechanical properties of tilt-cast Ti-45Al-5Nb-2C (at.%) alloy was investigated. Three alloys with nominal composition Ti-45Al-5Nb-2C-2X (in at.%), where X is Ta or W, were prepared by vacuum induction melting in graphite crucibles followed by tilt casting into graphite moulds. The microstructure of the tilt-cast alloys consists of the α2(Ti3Al) + γ(TiAl) lamellar grains, single γ phase, (Ti,Nb,X)2AlC particles with a small amount of (Ti,Nb,X)C, and β/B2 phase identified only in W containing alloy. The EDS analysis shows that Ta segregates into the carbide particles and reduces dissolution of Nb in both (Ti,Nb,Ta)C and (Ti,Nb,Ta)2AlC phases. The alloying with W reduces Nb content in both carbide phases and leads to stabilisation of β/B2 phase in the lamellar α2 + γ regions. The alloying with Ta and W does not affect the volume fraction of the carbide particles but influences their size and morphology. While the alloying with Ta and W has no significant effect on Vickers hardness and the indentation elastic modulus of the studied alloys, the addition of Ta affects the nanohardness and elastic modulus of the (Ti,Nb,Ta)2AlC phase. The addition of W significantly increases the Vickers microhardness of the lamellar α2 + γ regions.